Dexpramipexole blocks Nav1.8 sodium channels and provides analgesia in multiple nociceptive and neuropathic pain models. Issue 4 (April 2020) - Urru, Matteo; Muzzi, Mirko; Coppi, Elisabetta; Ranieri, Giuseppe; Buonvicino, Daniela; Camaioni, Emidio; Coppini, Raffaele; Pugliese, Anna Maria; Tanaka, Brian; Estacion, Mark; Waxman, Stephen G.; Dib-Hajj, Sulayman D.; et al.
Abstract : Abstract: Selective targeting of sodium channel subtypes Nav 1.7, Nav 1.8, and Nav 1.9, preferentially expressed by peripheral nociceptors, represents a unique opportunity to develop analgesics devoid of central side effects. Several compounds that target Nav 1.7 and Nav 1.8 with different degrees of selectivity have been developed and are currently being tested in clinical trials for multiple pain indications. Among these chemicals, benzothiazole-like compounds emerged as potent sodium channel blockers. We evaluated the effects of dexpramipexole, a benzothiazole-bearing drug with pleiotypic neuroactive properties and a good safety profile in humans, on sodium conductances of dorsal root ganglia neurons, as well as in multiple nociceptive and neuropathic pain models. Dexpramipexole blocks TTX-resistant sodium conductances in cultured rat dorsal root ganglion neurons with an IC50 of 294.4 nM, suggesting selectivity towards Nav 1.8. In keeping with this, dexpramipexole does not affect sodium currents in dorsal root ganglion neurons from Nav 1.8 null mice and acquires binding pose predicted to overlap that of the Nav 1.8 channel-selective blocker A-8034637. The drug provides analgesia when parenterally, orally, or topically applied in inflammatory and visceral mouse pain models, as well as in mice affected by neuropathic pain induced by oxaliplatin, nerve constriction, or diabetes. Pain reduction in mice occurs at doses consistent with those adopted in clinical trials. The present findings confirm the relevance of selective targeting of peripheral Nav 1.8 channels to pain therapy. In light of the excellent tolerability of dexpramipexole in humans, our results support its translational potential for treatment of pain. Abstract : Supplemental Digital Content is Available in the Text.The ability of dexpramipexole to selectively and potently block Nav 1.8 sodium channels is disclosed, thereby indicating its unexpected translational potential to treatment of pain.